The Flavonoids of Orophea polycarpa A. DC. (Annonaceae) - Lajis, Md Nordin; Khan, Mohamad Niyaz; Kiew, Ruth; Bremner, John B. (Universiti Putra Malaysia Press, 1993)
Investigation on the neutral fraction of the leaves of Oraphea polycarpa A. DC. led to the isolation of two flavonoids identified as 2'-hydroxy-4,4',6'trimethoxychalcone and 5,7,4'-trimethoxyflavanone.